2015
DOI: 10.1136/bmjopen-2015-007726
|View full text |Cite
|
Sign up to set email alerts
|

Why do patients with ‘primary care sensitive’ problems access ambulance services? A systematic mapping review of the literature

Abstract: ObjectiveEmergency ambulance use for problems that could be managed in primary care continues to rise owing to complex reasons that are poorly understood. The objective of this systematic review is to draw together published evidence across a variety of study methodologies and settings to gain a better understanding of why patients seek help from ambulance services for these problems.DesignSystematic searches were undertaken across the MEDLINE, EMBASE, PsychINFO, CINAHL, Health Management Information Consortiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
94
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(105 citation statements)
references
References 36 publications
5
94
0
6
Order By: Relevance
“…A calm and safe care creates a calm atmosphere that benefits the situation and the assessment. Booker, Shaw, and Purdy () suggest strategies to assist patients and bystanders in mitigating their perceptions of risk and state that we should be sensitive to the idea that patients and relatives might not know what type of help they need when they contact emergency care services. Rantala, Forsberg, and Ekwall () highlight that within ambulance care, also and maybe especially, when it is non‐emergency, the care should be person‐centred and always taking patients seriously.…”
Section: Discussionmentioning
confidence: 99%
“…A calm and safe care creates a calm atmosphere that benefits the situation and the assessment. Booker, Shaw, and Purdy () suggest strategies to assist patients and bystanders in mitigating their perceptions of risk and state that we should be sensitive to the idea that patients and relatives might not know what type of help they need when they contact emergency care services. Rantala, Forsberg, and Ekwall () highlight that within ambulance care, also and maybe especially, when it is non‐emergency, the care should be person‐centred and always taking patients seriously.…”
Section: Discussionmentioning
confidence: 99%
“…ambulances) when people could have their needs met in a PHC unit, revealed that the individual characteristics of patients and those of their caregivers (health condition, perception regarding the condition's level of severity, feelings such as anxiety or loneliness), aspects related to the services' infrastructure and organization (the adoption of models based on PHC, but also the prior experiences of users and their levels of satisfaction), as well as social factors (demographic and socioeconomic factors and whether the individual has health insurance) are factors that influence an individual's decision to seek this type of service. 12 In this sense, the authors state that considering the search for emergency services "inappropriate" to solve problems that could be solved in PHC units depends on the context and can be an innocuous approach when organizing health services. Hence, the focus of emergency services should be on strengthening screening strategies and classification of risk.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the focus of emergency services should be on strengthening screening strategies and classification of risk. 12 The city under study has a specific protocol to classify risks, according to which cases considered to be an emergency should be immediately taken care of in the emergency room; cases considered to be urgent situations deserve attention and should be assessed by a physician within 30 minutes; cases classified as intercurrences are less severe urgent care situations and can be taken care of within 60 minutes; and finally, outpatient cases are not urgent and can wait more than 120 minutes or be referred to a reference health unit after first contact. 13 Only 0.43% of the cases were classified as emergency and 7.95% were considered to be urgent matters, indicat-ing UPAs are not fulfilling their true mission, that of mainly providing care to urgent situations and emergencies, composing the emergency network, and rapidly and timely providing care to patients without losing sight of principles such as humanization and integral care.³ On the other hand, 44.09% of the patients were classified as intercurrences and 47.51% were considered to require outpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…The state of preservation of the ambulance helps in the care provided by the professionals to the patients, and may lead to inadequate assistance to the user, which may reflect their degree of satisfaction 16 .…”
Section: Discussionmentioning
confidence: 99%